(untitled) (Journal of Governance and Development (JGD), 2024)
Malaysia business environment was predominantly made up of small and medium enterprises (SMEs), which indicates a total of 1,151,339 SMEs that represent 97.2 percent of total business establishments. The SMEs created employment accounted for 7.25 million workforces, which indicates 48 percent of total employment in the year 2020. The unexpected outbreak of the COVID-19 pandemic has presented a notable challenge for numerous SMEs, particularly in developing nations that have been slower in implementing digitalization strategies. Without exception, SMEs in Malaysia are currently facing ongoing challenges in their efforts to undertake digital transformation. Despite the considerable advantages derived from the digitised economy, small and financially constrained SMEs continued to lag due to internal resource and information deficiencies, skills gaps, and challenges related to securing financing. Hence, this study aims to investigate the digital transformation phenomenon and the challenges faced by SMEs following the COVID-19 pandemic so that the government can provide the necessary support for SMEs’ digital transformation.